(untitled) (Indonesian Economic Justice Review, 2024)
This paper critically examines the role of Corporate Social Responsibility (CSR) in promoting economic justice in Indonesia, particularly through the actions of large corporations in the extractive, manufacturing, and retail sectors. Indonesia’s rapid industrialization and economic growth have been accompanied by environmental degradation, labor exploitation, and widening income inequality, which raises questions about the ethical obligations of corporations in addressing these issues. The study explores the scope and effectiveness of CSR initiatives by major Indonesian companies, focusing on their contributions to community development, environmental sustainability, and equitable economic opportunities. Using case studies from sectors such as palm oil, mining, and energy, the paper assesses whether CSR programs genuinely contribute to economic justice or merely serve as public relations tools. Additionally, it critiques the regulatory frameworks governing CSR in Indonesia, investigating the gaps in enforcement and accountability. The findings suggest that while some corporations have made notable contributions to local communities and environmental sustainability, CSR programs are often fragmented and insufficient in addressing the structural inequalities that perpetuate poverty and marginalization. The paper concludes with policy recommendations aimed at strengthening CSR regulations, enhancing transparency, and encouraging corporations to adopt more robust, systemic approaches to fostering economic justice.